Interaction between cardiac functional indices during incremental exercise test reveals the peculiarities of adaptation to exercising - Velicka, D.; Kairiukstiene, Z.; Poderiene, K.; Vainoras, A.; Poderys, J. (Medicina, 2019)
Background and objectives: Physical load causes structural changes in the heart that vary depending on the type of training and may affect the function of the heart. Aim of the study: To determine, using the applied co-integration method on algebraic data, the impact of sprinting and of endurance adaptation on the dynamic interactions of cardiovascular functional indices while participants were performing under an increasing workload, up to their inability to continue. Materials and Methods: Healthy athletes were chosen to take part in this study and were separated into two groups: Sprinters (n = 11) and endurance athletes (n = 13). The bicycle ergometric method of incremental increase in a provocative workload (graded stress) was used. The heart rate, stroke volume, and cardiac output were determined using the tetrapolar rheography method. Results: Individuals who are adapted to endurance while carrying physical loads, in contrast to well adapted sprinters, are characterized with a lower rate of changing the pace of interactions between stroke volume and cardiac output while performing at an increasing workload up to their inability to continue. Also, endurance athletes displayed a long and relatively stable phase as well as a greater decrease of interaction between indices at the end of the workload. At the beginning of the exercise, the interaction between the stroke volume and the cardiac output was reduced. However, as the physical load continued, this interaction became significantly stronger. The comparison of the stroke volume and the cardiac output`s dynamic interaction revealed that the endurance group had a greater working capacity. Conclusions: Typical dynamics of interactions during the testing with an increasing physical load can be differentiated into separate phases: The decrease of interaction at the onset of the load, the increase during the continuation of an increased workload, and the decrease at the last stages of the load